MENTAL HEALTH EDUCATION ON COMMUNITY THROUGH CMHN IMPLEMENTATION - Erna Erawati; Sri Adiyati; Angga Sugiarto (Jurnal LINK, 2016)
Kalegen village is a rural area with an area of 2.26 km2 and the population density in 1130 and has experienced landslides. Disaster, illness were stressor that can lead to mental disorders and risky if not handled well. The community service activity was aimed to implemented the results of research on mental health education in the community through the implementation of Community Mental Health Nursing (CMHN) so hopefully people have adaptive coping. The activities carried out for 50 hours in six hamlets in the village Kalegen Bandongan, Magelang. Question and answer drills, role play were conducted. Results: A 180 members of the community were participated. The decreased of symptoms of stress through the Self Reporting Questionnairre (SRQ) were reported. We found this action was effective for the community in instilling awareness of the importance of healthy mental life. Conclusion: This action support the implementation of the vision and mission of nursing studies program Magelang and provide supplies to students as a therapeutic tool in providing mental health nursing care. Suggestions: Changes the knowledge and ability to handle stress and be meaningful if people exercise consistently.